Peningkatan Keterampilan Berpikir Kritis Siswa Melalui Penerapan Model Generative Learning pada Materi Hukum Newton - Haris Rosdianto (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2018)
This study aimed to describe the improvement of students' critical thinking skills in Newton's Law subject after generative learning model was implemented. The type of this research was pre-experimental research with One Group Pretest-Posttest Design. The population of this study was all eighth grade students of MTs Makarim Al-akhlak, Singkawang City. The sampling technique used was saturated sampling. The research instrument used was a description test. The data obtained was not normally distributed, so the data was analyzed using non-parametric statistical test namely Mc Nemar Test. From the calculation results, it was obtained the value of χ2obs. > χ2c.v. or 6.125 > 3.841, then H0 was rejected and Ha was accepted at the significance level α = 0.05. Therefore, it could be concluded that there was an improvement in students' critical thinking skills in Newton's law subject after generative learning model was implemeted.